Identificação de genes com alta taxa evolutiva em tecidos reprodutivos femininos de moscas-das-frutas Anastrepha obliqua - Gonçalves, Vanessa Regina (Universidade Federal de São Carlos, 2010)
The genus Anastrepha is the largest in the family Tephritidae (Trypetinae, Toxotrypanini). The construction of cDNA libraries is important for identifying new genes and establishing genetic markers on non-models organisms such as the genus Anastrepha. Among the proteins involved in reproduction, we can cite those belonging cascade sexual and those responsible for forming the eggshell. The purpose of this study was to build a cDNA library from a pool of female reproductive tissues Anastrepha obliqua to breed ESTs, to search for genes with a high evolutionary rate, focusing on chorionic and vitelline proteins. We were sequenced 2304 clones obtained from the reproductive tissues of female flies Anastrepha obliqua. In total, 310 contigs and 506 singlets were generated wich were classified into different proteins classes. The chorionic proteins and Sxl revealed to be under selection positive as well as the vitelline Vm 26Aa ', which was possibly generated by a gene duplication of Vm 26aa, while Tra2 seems under purifying selection. The inference of the secondary structure of proteins studied revealed that the sites under positive selection were present on outside membrane. The population analysis of genes chorionic, vitelline, Sxl and Tra2 revealed no separation between the 3 species, although in some situations have occurred separation between some of the haplotypes for a single specie. With these results, it was possible to identify new genes, make the full sequencing for some vitelline and chorionic genes on pools of other species of Anastrepha, and we also identified that some of these genes are under positive selection pressure.
Keywords: Genética e evolução; Biblioteca de cDNA; Anastrepha; Seleção natural; CIENCIAS BIOLOGICAS::GENETICA